Data Visualization in Enlightenment Literature and Culture 2021
DOI: 10.1007/978-3-030-54913-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Early Modern Canon: The English Short Title Catalogue and Large-Scale Patterns of Cultural Production

Abstract: This chapter presents the findings of an ongoing digital project of the Helsinki Computational History Group at Helsinki Centre for Digital Humanities (HELDIG) focused on the history of eighteenth-century book publication. The authors have created a historical-biographical database based on The English Short-Title Catalogue (ESTC), a standard source for analytical bibliographic research, and extracted a data-driven canon which considers changes over time, subject-topics, top-works, authors, publishers, publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The full technical details of these harmonization and curation efforts for the ESTC catalogue are extensive, and instead of repeating them here we refer to our recent work that provides a more comprehensive description. 32 Hugh Amory claims that it is impossible to use the ESTC as a data resource for statistical analysis. 33 This has been sensibly countered by others, and we have demonstrated that bibliographical records can indeed be used for statistical purposes.…”
Section: Data Harmonization and Quantitative Comparisonmentioning
confidence: 99%
“…The full technical details of these harmonization and curation efforts for the ESTC catalogue are extensive, and instead of repeating them here we refer to our recent work that provides a more comprehensive description. 32 Hugh Amory claims that it is impossible to use the ESTC as a data resource for statistical analysis. 33 This has been sensibly countered by others, and we have demonstrated that bibliographical records can indeed be used for statistical purposes.…”
Section: Data Harmonization and Quantitative Comparisonmentioning
confidence: 99%